Relational model for the development of dynamic skills based on bibliometric analysis - Bonilla Rueda, Lina Rosenda; Rueda Galvis, Javier Francisco; Garavito Hernández, Youseline (Revista Venezolana de Gerencia, 2022)
This article exposes the formulation of a relational model that allows in any type of organization the practical development of the concepts proposed by the theory of Dynamic Capabilities, to be integrated as a management strategy that allows for increasing the levels of competitiveness and business survival, for which a qualitative study was carried out under the methodology of bibliometric analysis and documentary review of more than 500 relevant scientific documentary sources through an analytical and interpretive synthesis of the most significant arguments. Among the most important results of this study, it stands out the power to establish the most representative results of recent years, a relational model that identifies each of the steps and key factors that any type of organization must develop, to achieve the postulates that it exposes. The theory of dynamic capabilities is based on concepts such as organizational learning, absorbing knowledge, innovation, value-added, adaptability, business competitiveness, internationalization, and survival.